GEOMATE PROJECT : Implementation of Project Based Learning (PjBL) with STEAM approach in producing geometry transformations totebags as fashion products - Sizillia Noranda Mayangsari (Journal of Education and Learning Sciences, 2026)
This study aims to describe the implementation of the "GEOMATE PROJECT" in enhancing students motivation and conceptual understanding of geometric transformations in Advanced Mathematics. The research employed a comprehensive methodology, including activity observation and in-depth interviews, to ensure accurate results. The study was prompted by low student motivation, with initial data showing only 52% interest in Matematika Tingkat Lanjut, largely due to the perception that the subject focuses solely on numerical calculations and rote memorization. The learning model utilized was Project-Based Learning (PjBL) integrated with a STEAM (Science, Technology, Engineering, Art, and Mathematics) approach and differentiated instruction. In this project, students designed and produced unique tote bags by applying the principles of translation, rotation, dilation, and reflection. Differentiation was implemented across three dimensions: content (freedom in sketching while maintaining geometric concepts), process (choice of conventional or digital design), and product (selection of screen printing or manual painting techniques) based on students' interests and abilities. The results indicate that the "GEOMATE PROJECT" significantly increased learning motivation, strengthened conceptual understanding of geometry, and developed essential 21st-century skills, including critical thinking, creativity, collaboration, and communication. The STEAM approach, integrated with tangible products, created a meaningful, innovative, and relevant learning experience, increasing student interest in Matematika Tingkat Lanjut to 84%. Beyond mastering geometric transformations, students gained proficiency in digital and manual arts, material science (selecting durable pigments), and textile selection. This interdisciplinary involvement fostered higher motivation, as students realized that integrating various fields of knowledge significantly enhances the quality of a final product.